Pesona Alam dalam Fotografi Landscape dalam Kerangka Analisis Isi - Moch. Astya Ariya Rahmansyah (Universitas Merdeka Malang, 2023)
The choice of nature as a space for exploration, including mountains, sea and rice fields in the creation of works of art is because nature is an entity that cannot be separated from human life. The creator of this work uses observation and experimentation methods to be able to visualize nature through landscape photography. This research method is descriptive qualitative by analyzing the contents of photos and compositions. The research steps include preferences, experimental analysis and detour analysis. The choice of nature as a space for exploration, including mountains, seas and rice fields in the creation of works of art means that nature is an entity that cannot be separated from human life. Within the framework of photography techniques, it can give birth to a variety of imaginations when explored, especially through the art medium of photography.